Ho Chi Minh’s viewpoint on cononialism - Thanh, Pham Quoc (VNU Journal of Science: Social Sciences and Humanities; Vol 27 No 3, 2011)
Abstract. Ho Chi Minh-the hero o f Vietnam national liberation, the worid eminent man o f culture.He is one of ứie most influential political figures of the twentieth century. His thought is a great spiritual asset o f the Party and the nation, is a great dedication, contributing to enriching thehuman Measure o f culture and ideology. One o f his outstanding contributions to Vietnam'srevolution and the world is he has identified sharply, precisely the evil nature o f colonialism.Through his speeches and writings, Ho Chi Minh has criticized the French colonialism inparticular, and colonialism in general in a comprehensive way. On every aspect, he gave thespecific, vivid evidence on the ruthlessness and oppression o f colonialism, especially French colonists to strongly denounce their crimes. On the basis o f condemning colonialism and clearly identifying its reactionary nature, Ho Chi Minh called for oppressed nations and people in colonized nations and proletariat in metropolitan countries to struggle against a common enemy - colonialism. In this aspect, Ho Chi Minh had a great theoretical devotion to the world national liberation movement and proletarian revolution. This artical focuses on analyzing Ho Chi Minh's viewpoint on colonialism to contribute to demonstrating the correcữiess of Vieứiam national liberation revolution path.